Common Uses and Adverse Effects of Hyperbaric Oxygen Therapy in a Cohort of Small Animal Patients: A Retrospective Analysis of 2,792 Treatment Sessions - Montalbano, Christina; Kiorpes, Caroline; Elam, Lindsay; Miscioscia, Erin; Shmalberg, Justin (Frontiers in Veterinary Science, 2021)
Hyperbaric oxygen therapy (HBOT) is commonly utilized for various human conditions with a low incidence of major adverse effects (0.002-0.035%). Despite growing use in veterinary patients, there remains a paucity of literature describing its use and associated complications. The purpose of this study was to report clinical use of HBOT in small animals and identify the rate of major adverse events at a university teaching hospital. Electronic medical records were searched for small animals receiving HBOT between November 2012 and February 2020. Data extracted from the medical records included signalment, treatment indication, and adverse events. Treatment sessions totaled 2,792 in 542 dogs, 24 cats, and 10 pocket pets and exotics. Common indications included neurologic injuries (50.4%), tissue healing (31.4%), control of oomycete infection (5.5%), neoplasia or post-radiation injury (5.4%), and various miscellaneous conditions (7.4%). Observed minor adverse events included agitation in 2 dogs and vomiting in 3 dogs. The most common major adverse event was central nervous system (CNS) oxygen toxicity in 19 dogs. CNS oxygen toxicity, manifesting as focal or generalized seizures, occurred in 0.7% of treatment sessions, with increasing age (p=0.01) and female sex (p=0.01) identified as risk factors. One dog developed pulmonary edema following HBOT which is a reported adverse event in humans or may have been a manifestation of progression of the dog’s underlying disease. No adverse events were noted in cats or other species. In conclusion, HBOT appeared safe across various indications, although oxygen toxicity affecting the central nervous system was higher than reports in humans. Future prospective, randomized, controlled trials should evaluate specific clinical indications and outcomes.